What are the demographic and clinical differences between those older adults with traumatic brain injury who receive a neurosurgical intervention to those that do not? A systematic literature review with narrative synthesis. (7th June 2022) - Barrett, Jack W.; Williams, Julia; Griggs, Joanna; Skene, Simon; Lyon, Richard
ABSTRACT: Objectives: This review aimed to identify the demographic and clinical differences between those older adults admitted directly under neurosurgical care and those that were not, and whether EMS clinicians could use these differences to improve patient triage. Methods: The authors searched for papers that included older adults who had suffered a TBI and were either admitted directly under neurosurgical care or were not. Titles and abstracts were screened, shortlisting potentially eligible papers before performing a full-text review. The Newcastle-Ottawa Scale was used to assess the risk of bias. Results: A total of nine studies were eligible for inclusion. A high abbreviated injury score head, Marshall score or subdural hematoma greater than 10 mm were associated with neurosurgical care. There were few differences between those patients who did and did not receive neurosurgical intervention. Conclusions: Absence of guidelines and clinician bias means that differences between those treated aggressively and conservatively observed in the literature are fraught with bias. Further work is required to understand which patients would benefit from an escalation of care and whether EMS can identify these patients so they are transported directly to a hospital with the appropriate services on-site.